Revitalisasi Objek Wisata Melalui Pendekatan Asset Based Community Development (ABCD) - Parman, Parman; Ismail, Ismail (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
Lampu Satu beach tourism is an icon of beach attractions in Merauke regency which has strategic value. This research aims to optimize existing coastal tourism potential assets so that they can grow sustainably through the Asset Based Communities Development (ABCD) approach. The ABCD approach aims to maximize the potential of physical and non-physical assets at the location of the Lampu Satu tourist attraction. The type of research is qualitative with primary data through data collection techniques, namely observation and in-depth interview interviews, which are then analyzed with a descriptive analysis approach, while secondary data comes from literature reviews both from books and journals that are related and relevant to the substance of the research conducted. The results showed that on Lampu Satu Merauke beach, there are several assets that have not been optimized such as historical assets, individual assets, facilities and infrastructure and natural resource assets. One of the other efforts to maximize other tourism potential is to increase social media understanding and digital access to tourism managers, as a tourism promotion tool. In addition, education and socialization about the management of organic waste into compost is part of the sustainable tourism development process.